Does Generation Matter? – Changing the Church from the Inside - Johansen, Kirstine Helboe (International journal of practical theology, 2018)
In this article, possible generational differences between younger and older pastors in the Evangelical-Lutheran Church in Denmark are examined with respect to their understandings of the wedding and the ecclesiological implications of these understandings. Building on the generational theory of Karl Mannheim, the hypothesis is that despite in-group similarities between older and younger pastors, the two generations will show differences in the way they represent their office and thereby the church is changed not only from the outside but also from the inside. An explorative qualitative study of the understanding of the wedding among selected pastors investigates their understanding of the wedding service in three different dimensions and shows that both groups primarily understand the wedding as a traditional ritual, but younger pastors appear to enact this understanding in a relational approach in which the meaning of the wedding emerges in the encounter between pastor and wedding couple. The older pastors appear to link the meaning of the wedding closely to the ritual procedures themselves. At the end of the article, the ecclesiological implications of these different understandings of the wedding service are elaborated.